Endothelial Cell‐Derived Extracellular Vesicles Promote Aberrant Neutrophil Trafficking and Subsequent Remote Lung Injury - Shuang‐Feng Zi; Xiao‐Jing Wu; Ying Tang; Yun‐Peng Liang; Xu Liu; Lu Wang; Song‐Li Li; Chang‐De Wu; Jing‐Yuan Xu; Tao Liu; Wei Huang; Jian‐Feng Xie; et al. (Advanced Science)
Abstract The development of acute respiratory distress syndrome (ARDS) in sepsis is associated with substantial morbidity and mortality. However, the molecular pathogenesis underlying sepsis‐induced ARDS remains elusive. Neutrophil heterogeneity and dysfunction contribute to uncontrolled inflammation in patients with ARDS. A specific subset of neutrophils undergoing reverse transendothelial migration (rTEM), which is characterized by an activated phenotype, is implicated in the systemic dissemination of inflammation. Using single‐cell RNA sequencing (scRNA‐seq), it identified functionally activated neutrophils exhibiting the rTEM phenotype in the lung of a sepsis mouse model using cecal ligation and puncture. The prevalence of neutrophils with the rTEM phenotype is elevated in the blood of patients with sepsis‐associated ARDS and is positively correlated with disease severity. Mechanically, scRNA‐seq and proteomic analys revealed that inflamed endothelial cell (EC) released extracellular vesicles (EVs) enriched in karyopherin subunit beta‐1 (KPNB1), promoting abluminal‐to‐luminal neutrophil rTEM. Additionally, EC‐derived EVs are elevated and positively correlated with the proportion of rTEM neutrophils in clinical sepsis. Collectively, EC‐derived EV is identified as a critical regulator of neutrophil rTEM, providing insights into the contribution of rTEM neutrophils to sepsis‐associated lung injury.